Discovery of an MLLT1/3 YEATS Domain Chemical Probe. Issue 50 (16th November 2018) - Moustakim, Moses; Christott, Thomas; Monteiro, Octovia P.; Bennett, James; Giroud, Charline; Ward, Jennifer; Rogers, Catherine M.; Smith, Paul; Panagakou, Ioanna; Díaz‐Sáez, Laura; Felce, Suet Ling; Gamble, Vicki; et al.
Abstract: YEATS domain (YD) containing proteins are an emerging class of epigenetic targets in drug discovery. Dysregulation of these modified lysine‐binding proteins has been linked to the onset and progression of cancers. We herein report the discovery and characterisation of the first small‐molecule chemical probe, SGC ‐iMLLT, for the YD of MLLT1 (ENL/YEATS1) and MLLT3 (AF9/YEATS3).SGC‐iMLLT is a potent and selective inhibitor of MLLT1/3–histone interactions. Excellent selectivity over other human YD proteins (YEATS2/4) and bromodomains was observed. Furthermore, our probe displays cellular target engagement of MLLT1 and MLLT3. The first small‐molecule X‐ray co‐crystal structures with the MLLT1 YD are also reported. This first‐in‐class probe molecule can be used to understand MLLT1/3‐associated biology and the therapeutic potential of small‐molecule YD inhibitors. Abstract : Molecular poetry : YEATS domain (YD) containing proteins are an emerging class of epigenetic protein targets in drug discovery. A screening hit has been developed into the first potent, selective, and cell‐active chemical probe for the YD‐containing proteins MLLT1 and MLLT3. The probe represents the first inhibitor of its class to explore YD‐associated biology and disease links.